Deccan Traps Volcanism Implicated in the Extinction of Non‐Avian Dinosaurs in Southeastern China - Ma, Mingming; Zhang, Wenfang; Zhao, Mengting; Qiu, Yudan; Cai, Hongming; Chen, Jiubin; Liu, Xiuming (Geophysical research letters, 2022)
The extinction of non‐avian dinosaurs and its cause(s) have been a matter of debate for several decades. Here we measured Hg and its isotopic composition, heavy metals, and magnetic parameter in a terrestrial basin in southeastern China. Hg exhibited anomalies from 66.4 to 65.6 Ma, with near‐zero to positive Δ199Hg values, which reflected the eruption of Deccan Traps (DT) magma. In addition, Hg anomalies coincided with the gradual extinction of non‐avian dinosaurs, thereby consistent with the hypothesis that DT played a key role in the mass extinction. Analysis of paleoclimatic records showed that both the Late Maastrichtian warming event (LMWE) and Dan‐C2 event occurred at the maxima of the 405‐kyr long eccentricity cycle, and the onset of the dinosaur decline was earlier than the LMWE, suggesting that the LMWE played an ancillary role in the mass extinction. The mechanism of how DT caused the mass extinction requires further investigation. Plain Language Summary The debate concerning the relative importance of the Chicxulub bolide impact and/or Deccan Traps (DT) volcanism as the cause of the extinction of non‐avian dinosaurs at the end of the Cretaceous has lasted for several decades. There is lack of direct geological evidence linking the DT eruption with the non‐avian dinosaur fossil record, so the Chicxulub bolide impact is regarded by many as the dominant—if not the sole—cause of the mass extinction. Therefore, it is necessary to find new geological evidence to clarify this issue. In this study, the concentration of Hg and its isotope systematics were carefully investigated, combined with palaeontology data and palaeoclimate records, we suggest that DT played a key role in the extinction of non‐avian dinosaurs. Key Points Hg combined with its isotopic composition indicate the record of Deccan Traps (DT) volcanism DT volcanism played an important role in the extinction of non‐avian dinosaurs The inherent mechanism of how DT caused the mass extinction requires further investigation